The current state of the art in internal additive materials and quantum dots for improving efficiency and stability against humidity in perovskite solar cells. Issue 12 (December 2022) - Sanglee, Kanyanee; Nukunudompanich, Methawee; Part, Florian; Zafiu, Christian; Bello, Gianluca; Ehmoser, Eva-Kathrin; Chuangchote, Surawut
Abstract: The remarkable optoelectronic capabilities of perovskite structures enable the achievement of astonishingly high-power conversion efficiencies on the laboratory scale. However, a critical bottleneck of perovskite solar cells is their sensitivity to the surrounding humid environment affecting drastically their long-term stability. Internal additive materials together with surface passivation, polymer-mixed perovskite, and quantum dots, have been investigated as possible strategies to enhance device stability even in unfavorable conditions. Quantum dots (QDs) in perovskite solar cells enable power conversion efficiencies to approach 20%, making such solar cells competitive to silicon-based ones. This mini-review summarized the role of such QDs in the perovskite layer, hole-transporting layer (HTL), and electron-transporting layer (ETL), demonstrating the continuous improvement of device efficiencies. Graphical abstract: Image 1 Highlights: Surface passivation, polymer-mixed perovskite, and quantum dots (QDs) as strategies to enhance stability have been reviewed. QDs implemented in perovskite sheets, HTLs, and ETLs demonstrate improvements in the efficiency of perovskite solar cells. The implementation of QDs results in the reduction of recombination pathways, resulting in the long-term stability of devices. Abstract : Electron transporting layer; Hole transporting layer; Passivation; Perovskite solar cells; Quantum dots; Stability.